Getting the basic rights - the role of water, sanitation and hygiene in maternal and reproductive health: a conceptual framework - M. R. Campbell, Oona; Benova, Lenka; Gon, Giorgia; Afsana, Kaosar; Cumming, Oliver (© 2015 Blackwell Publishing Ltd, 2017)
This article was published in Tropical Medicine and International Health [ © 2015 Blackwell Publishing Inc.] and the definite version is available at: http://onlinelibrary.wiley.com/doi/10.1111/tmi.12439/abstract